2003
DOI: 10.1177/1464884903004002021
|View full text |Cite
|
Sign up to set email alerts
|

Who are these guys? The online challenge to the notion of journalistic professionalism

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link: WHO ARE THOSE GUYS?The online challenge to the notion of journalistic professionalism Jane B. Singer WHO ARE THOSE GUYS? The online challenge to the notion of journalistic professionalismThe people who claim membership in a profession and delineate its attributes do so at least in part to justify inequality of status, as well as to limit and control access to that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
169
0
16

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(187 citation statements)
references
References 7 publications
2
169
0
16
Order By: Relevance
“…This empowering of journalistic agency is supported by recent observations of news production, argues Cottle. It also seems to be a fruitful position to adopt in this period of media transition, especially since the role of the journalist today is undergoing substantial change entailing a more individualized line of work in which journalists are expected to master a greater variety of tasks and skills (Deuze 2005, Nygren 2008, Singer 2003. Paying closer attention to the practice of journalists is also crucial if one aims to bridge the gap between journalism practitioners and scholars.…”
Section: Three Perspectives Of Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…This empowering of journalistic agency is supported by recent observations of news production, argues Cottle. It also seems to be a fruitful position to adopt in this period of media transition, especially since the role of the journalist today is undergoing substantial change entailing a more individualized line of work in which journalists are expected to master a greater variety of tasks and skills (Deuze 2005, Nygren 2008, Singer 2003. Paying closer attention to the practice of journalists is also crucial if one aims to bridge the gap between journalism practitioners and scholars.…”
Section: Three Perspectives Of Innovationmentioning
confidence: 99%
“…In a survey of US journalists and editors, Singer (1997) found that most journalists believed new technology would not affect the way they did their job. The respondents' answers were clearly influenced by an assumption that their newsroom work culture would not be affected by the new medium, thus discarding the need for extensive innovation.…”
Section: Innovation In Online Newsroomsmentioning
confidence: 99%
“…Among the issues he highlights with implications inside converged newsrooms are conflicts of interest among media partners and plagiarism, with its associated concerns about authenticity, authorship, and accuracy. In considering online challenges to professionalism, Singer (2003) suggests that a medium with few gatekeepers, "in which deadlines are perpetual and competition is intense," can create enormous pressure to run stories before they are verified (p. 152). Cohen (2002) examines the dynamics of online journalism at various levels, warning that market-driven concerns may dominate the new medium; in particular, demands for continuous updates can compromise accuracy and standards of newsworthiness.…”
Section: Selected Normative Researchmentioning
confidence: 99%
“…Online journalism is still in the process of establishing its own professional credentials (Singer, 2003) and does not have an ethics code per se. However, the mission statement of the Online News Association (2004), an organization formed in 1999 by and for journalists "whose principal livelihood involves gathering or producing news for digital presentation," lays out a set of "founding principles.…”
mentioning
confidence: 99%
“…However, much of the evidence for this 'power' comes from observations of how audiences actively interpret mass media messages (Morley, 1993) rather than how they interact directly with the communications channel. The frequent references to the audience's ability to make "decisions about how and when to access news content" (Meikle, 2009), and to power shifting "away from the professional and towards the layperson" (Singer, 2003), have not dispelled doubts about the extent to which established "passive" (Neuman, 1991: 42) patterns of media consumption are changing.…”
Section: News Consumption and Content Diversitymentioning
confidence: 99%